Any better? A follow-up content analysis of adolescent sexual and reproductive health inclusion in Global Financing Facility country planning documents - Ulla Walmisley; Mary V. Kinney; Joël Arthur Kiendrébéogo; Yamba Kafando; Asha S. George (Taylor & Francis Group, 2024)
Background The Global Financing Facility (GFF) supports national reproductive, maternal, newborn, child, adolescent health, and nutrition needs. Previous analysis examined how adolescent sexual and reproductive health was represented in GFF national planning documents for 11 GFF partner countries. Objectives This paper furthers that analysis for 16 GFF partner countries as part of a Special Series. Methods Content analysis was conducted on publicly available GFF planning documents for Afghanistan, Burkina Faso, Cambodia, CAR, Côte d'Ivoire, Guinea, Haiti, Indonesia, Madagascar, Malawi, Mali, Rwanda, Senegal, Sierra Leone, Tajikistan, Vietnam. Analysis considered adolescent health content (mindset), indicators (measure) and funding (money) relative to adolescent sexual and reproductive health needs, using a tracer indicator. Results  Countries with higher rates of adolescent pregnancy had more content relating to adolescent reproductive health, with exceptions in fragile contexts. Investment cases had more adolescent content than project appraisal documents. Content gradually weakened from mindset to measures to money. Related conditions, such as fistula, abortion, and mental health, were insufficiently addressed. Documents from Burkina Faso and Malawi demonstrated it is possible to include adolescent programming even within a context of shifting or selective priorities. Conclusion Tracing prioritisation and translation of commitments into plans provides a foundation for discussing global funding for adolescents. We highlight positive aspects of programming and areas for strengthening and suggest broadening the perspective of adolescent health beyond the reproductive health to encompass issues, such as mental health. This paper forms part of a growing body of accountability literature, supporting advocacy work for adolescent programming and funding.